Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) terhadap Pemberian Pupuk Organik Cair Limbah Pisang Kepok - Hilda Karim; Andi Irma Suryani; Yusnaeni Yusuf; Nur Afni Khaer Fatah (Universitas Negeri Makassar, 2019)
This study aims to study the effect of banana (Musa paradisiaca forma typica) liquid organic fertilizer on the growth of chili (Capsicum frutescens L.). Based on the results of the study, the dose of organic fertilizer increased for vegetative growth (growth of root length, stem height and number of leaves of chili) while in generative growth (average number of flowers, number of fruits, many plants, and many plants), chili plants produce facts, produces large quantities, number of plants, wet weight of plants, and wet weight of chili.